2014
DOI: 10.2989/16085906.2014.943254
|View full text |Cite
|
Sign up to set email alerts
|

The economics, financing and implementation of HIV treatment as prevention: What will it take to get there?

Abstract: The 2013 Lancet Commission Report, Global Health 2035, rightly pointed out that we are at a unique place in history where a "grand convergence" of health initiatives to reduce both infectious diseases, and child and maternal mortality--diseases that still plague low income countries--would yield good returns in terms of development and health outcomes. This would also be a good economic investment. Such investments would support achieving health goals of reducing under-five (U5) mortality to 16 per 1000 live b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 51 publications
1
13
0
Order By: Relevance
“…Although the increasing coverage of HIV testing in Brazil gives some indication that people are generally open to routine HIV screening, as HIV testing in antenatal care for pregnant women, known benefits of early treatment are outweighed by a perceived burden related to stigma and fear of being positive [52][53][54]. The Brazilian Behavioral Surveillance Survey, 2012 found that more than 60% of those with self-evaluation of high HIV infection risk had never tested for HIV.…”
Section: Discussionmentioning
confidence: 99%
“…Although the increasing coverage of HIV testing in Brazil gives some indication that people are generally open to routine HIV screening, as HIV testing in antenatal care for pregnant women, known benefits of early treatment are outweighed by a perceived burden related to stigma and fear of being positive [52][53][54]. The Brazilian Behavioral Surveillance Survey, 2012 found that more than 60% of those with self-evaluation of high HIV infection risk had never tested for HIV.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that ART is cost-effective not only for the purpose of keeping people alive but also because of its prevention benefits (Kahn et al, 2011;Loubiere et al, 2010;Wilson et al, 2014). Considering the prevention and treatment benefits, ART is a highly favourable intervention.…”
Section: Effectiveness and Cost-effectiveness Of Artmentioning
confidence: 96%
“…(D. P. Wilson et al, 2015) According to one estimate, implementing and maintaining a SEP costs approximately $23-$71 per person accessing services per year. (D. Wilson et al, 2014) Further, one study found that in addition to significantly reducing HIV incidence, a SEP reported an approximate $5 saved as a result of infection aversion for every $1 invested in providing services. (Kwon et al, 2009) Moreover, considering the cost of treating new cases of HIV (~$136 million per year) and HCV (~$176 million per year) just among PWID, the economic benefits of having optimal coverage of SEP could be profound.…”
Section: Care Access Utilization and Economic Impact Of Idumentioning
confidence: 99%
“…(Van Handel et al, 2016) Highly effective and cost containing public health interventions to counter IDU associated events have been identified in both rural and urban areas of the world, including syringe and injection equipment exchange programs (SEP). (Kwon, Iversen, Maher, Law, & Wilson, 2009;D. Wilson, Taaffe, Fraser-Hurt, & Gorgens, 2014;D.…”
Section: H a P T E R 1 : Introductionmentioning
confidence: 99%
See 1 more Smart Citation